Studi Komparatif Program Pengendalian Hama Terpadu Terhadap Pengetahuan, Produksi, Dan Pendapatan Petani Padi Sawah Di Kabupaten Labuhanbatu Utara - Zakiyah, Baratuj; Kuswardhani, Retno Astuti; Ginting, Rahmanta (Universitas Medan Area, 2019)
This study aims to understand the role of the SLPHT program in increasing farmers' knowledge and for the analysis of income and rice income in farmers collecting SLPHT with non-SLPHT farmers in North Labuhanbatu Regency. The study used a survey method and was carried out in North Labuhanbatu Regency for 3 (three) months, starting in April 2016 until June 2016. The number of research samples were 150 lowland rice farmers analyzed using statistics using average difference analysis (T test analysis) using SPPS software version 19. Results of research conducted with farmers who developed SLPHT, lowland rice, average prices average of 4,74 tons / hectare / planting season (tons / ha / MT). There is no significant difference in production and income between farmers collecting SLPHT and non-SLPHT. However, there is a difference in production between 500 Kilograms / Ha / MT. Regional related to farmers. SLPHT has a higher paddy production of 500 kg / ha / MT. The results of statistical analysis, average, average, income, farmers, SLPHT, much greater Rp. 1,060,113 from non-SLPHT farmers. The results of this study also found that the SLPHT program could broaden farmers' perspectives in agriculture.